Psychological Resilience, Mental Health, and Inhibitory Control Among Youth and Young Adults Under Stress - Afek, Anat; Ben-Avraham, Rina; Davidov, Alexander; Berezin Cohen, Noa; Ben Yehuda, Ariel; Gilboa, Yafit; Nahum, Mor (Frontiers in Psychiatry, 2021)
Psychological resilience allows one to cope successfully with adversities occurring during stressful periods, which may otherwise trigger mental illness. Recent models suggest that inhibitory control (IC), the executive control function which supports our goal-directed behavior and regulates our emotional response, may underlie resilience. However, the ways in which this is manifested during stressful situations in real life is still unclear. Here, we examined the relationship between IC, psychological resilience, psychological distress, and anxiety among 138 female and male participants in a stressful situation: during their initial combat training in the military. Using a mobile app, we assessed IC using emotional and non-emotional variations of the Go/No-Go task. Psychological resilience, psychological distress, and anxiety were assessed using mobile versions of self-report questionnaires. We found that psychological resilience is significantly correlated with non-emotional IC (r = 0.24, p < 0.005), but not with emotional IC; whereas, psychological distress and anxiety are correlated with emotional IC (r = −0.253, p < 0.005 and r = −0.224, p < 0.01, for psychological distress and anxiety, respectively), but not with non-emotional IC. A regression model predicting emotional IC confirmed non-emotional IC and distress as unique contributors to the variance, but not psychological distress. In addition, associations between psychological distress and emotional IC were found only for female participants. Collectively, the results clarify the link between IC, resilience, and mental health in real-life stressful situations, showing separate mechanisms of IC involved in resilience on the one hand, and mental health on the other hand. These results have implications for building mobile resilience interventions for youth and young adults facing stressful situations.